Effects of Spiritual Counseling on Spiritual Health-Quality of Life in Patients with HIV/AIDS - Hasanah, Ulung; Ibrahim, Kusman; Sriati, Aat (Department of Nursing, Faculty of Medicine, Diponegoro University, 2019)
Background: HIV/AIDS is a chronic and progressive disease that has complex health problems which affect the quality of life. Patients with HIV/AIDS need spiritual support to increase their spiritual health. A more effective therapeutic approach using spiritual counseling is seen as effective for improving health in chronic conditions.Purpose: This study aimed to examine the effects of spiritual counseling on the quality of life-spiritual health in patients with HIV/AIDS.Methods: This study employed a pre-posttest quasi-experimental design with a control group. The samples were 30 patients each in the experimental group and the control group recruited using purposive sampling. The experimental group received three sessions of spiritual counseling intervention. Data of the quality of life-spiritual health were collected using the WHOQOL-SRPB BREF and analyzed using t-test with significance <0.05. Â Results: Results indicated significant differences in the spiritual health-quality of life between the control and experimental groups. The result of paired t-test before and after the intervention in the experimental group showed a p-value of <0.05, whereas in the control group, the p-value was >0.05. After the intervention, the p-value in the experimental and control groups was <0.05, indicating significant differences between the two groups.Conclusion: This study concluded that spiritual counseling interventions had an effect on increasing the quality of life-spiritual health in patients with HIV/AIDS. Thus, it is necessary for the hospital to consider the results of this study as one of the interventions in providing nursing care to HIV/AIDS patients.